Functional convergence in water use of trees from different geographical regions: a meta-analysis - Kallarackal, Jose; Reineking, Björn; Jung, Eun-Young; Schmidt, Mark W. T.; Granier, André; Ochuodho, Dennis O. (Springer-Verlag Berlin Heidelberg, 2013)
Functional convergence in water use of trees across species from diverse geographic locations was examined using data on tree water use parameters, with the intention of gaining an understanding on the capacity for water transport for trees with varying structural and functional traits. Wood density (ρw), which is reported to have a negative exponential relation with sap flow density (SFD), showed a bell-shaped curve when the daily SFD data from 101 tree species belonging to 35 angiosperm and gymnosperm families were plotted. The species came from 23 different geographical locations representing all continents. Trees were most efficient in water transport when the ρw was between 0.51 and 0.65 g cm−3. When the ρw increased or decreased from this range, there was a gradual fall in their water transport rate as indicated by lower daily SFD. The unexpected reduction in SFD with decreasing ρw is explained in terms of reduced conductance in the transport pathway, which is a precaution taken by the tree for avoiding cavitation or implosion in larger conducting tubes, which is characteristic of low density wood. The development of severe leaf water potential variations, which is frequently reported in such trees, supports this notion. The SFD versus ρw relation has a potentially wide applicability in predicting water use by forest stands with varying ρw. In addition, the occurrence of a high number of tree species with ρw values in the range of 0.51–0.65 g cm−3across all continents examined points towards the importance of ρw in the evolutionary process as related to efficient functioning of the water transport mechanism.
Keywords: Sapflow density; Transpiration; Tree water use; Wood density; Water transport